Asteroids and Dwarf Planets and How to Observe Them - Dymock, Roger (Astronomers' Observing Guides, 2010)
ASTRONOMERS' OBSERVING GUIDES provide up-to-date information for amateur astronomers who want to know all about what it is they are observing. This is the basis of the first part of the book. The second part details observing techniques for practical astronomers, working with a range of different instruments. ------------------------------------------------------------------------------------------------------ We live in a violent universe. The media constantly remind us of the possibility of an object suddenly appearing and hitting Earth. A hit by an asteroid is believed to have spelled the end of the dinosaurs. Such a collision by an object from space could cause another extinction event, if the object were large enough. And such objects are definitely out there. Often called "the vermin of the sky," asteroids roam our Solar System often unseen. Many have been tracked, and their orbits calculated. But there are still many to be discovered and assessed. Many amateur astronomers are helping in this effort, sometimes even working with professional astronomers, to contribute to our knowledge and avert danger. Some people just enjoying locating these or the dwarf planets, such as Pluto, and then following their paths. Whatever your interest, Asteroids and Dwarf Planets and How to Observe Them will help you get started. It will tell you what you are looking at and why you should look. It will also help you learn how to look. This is definitely an area where amateurs can make a difference. Roger Dymock, in clear, engaging language can help you get started right now!